The Impact of Land Rights on Deforestation in Lao PDR - Vangxaolee, Khammai; Yangchiakoua, Duangpanya; Her, Prada; Kyophilavong, Phouphet (International Journal of Multidisciplinary in Management and Tourism, 2020)
The purpose of this study is to examine whether land rights reduces the deforestation in Lao PDR. The authors use secondary data that collected by LECS 5 (Lao Expenditure and Consumption Survey 5) in 2012-2013 from Lao Statistics Bureau and use 6,020 sample households in Laos. Logistic regression model is used for the analysis. This study finds that household land rights have a negative impact on deforestation (cutting timbers in surrounding forests) and the impact is statistically significant. The authors conclude that land rights of the households have a huge impact on deforestation in Lao PDR.Land use policy-makers should be aware that land rights and land security hugely reduce the deforestation (cutting of timbers of the households) especially rural households. This finding might have significant impacts on reducing deforestation by households in Lao PDR and provide information for further research in this area. It is the first study to investigate the impact of land rights on deforestation (cutting timbers in surrounding forests by households in Lao PDR) in the Faculty of Economic and Business Management, National University of Laos.